Influence of prolonged cryopreservation on the number and functional activity of stem/progenitor cells derived after G-CSF mobilization from patients with chronic heart failure - Н. А. Бондаренко; А. П. Лыков; О. В. Повещенко; А. Ф. Повещенко; Е. А. Покушалов; А. М. Караськов; В. И. Коненков; И. И. Ким; А. Б. Романов (Патология кровообращения и кардиохирургия, 2015)
Objectives and Methods. It is shown that long-term cryopreservation for 2 and 4 years leads to a reduction in the number and viability of the mononuclear cells obtained after mobilization granulocyte colony-stimulating factor (G-CSF) from patients with chronic heart failure. In addition, during prolonged cryopreservation decreased amount of content endothelial progenitor cells of the mononuclear cells from patients with chronic heart failure. Results. It was established that in cryopreservation for 2 and 4 years leads to a decreased proliferative activity of the mononuclear cells mobilized by G-CSF, both spontaneous and mitogen stimulated, increase cell number in the stage of apoptosis. The findings suggest that the negative impact on the long cryopreservation mononuclear cells obtained after G-CSF mobilization and effective cell therapy for heart failure patients need to use cells in the cryopreservation of not more than 2 years.